Analysis of students' interest in learning volleyball games - Muammar Azzun Alfathi; Gatot Margisal Utomo; Santika Rentika Hadi; Eka Kurnia Darisman (Sriwijaya Journal of Sport, 2025)
Research Problems: This study was conducted due to the low psychomotor skills of students in the practice of volleyball games. This lack of skills is closely related to the lack of student interest in learning, which could be influenced by teaching methods that are less varied and less interesting. Research Objectives: This study aims to analyze the level of student interest in volleyball learning in class VII MTs Darul Ulum Waru. Methods: The research method used was a survey with a descriptive quantitative approach. The research subjects involved grade 8A and 8B students with a total of 60 students. Data were collected using questionnaires and documentation. The analysis technique used is quantitative descriptive analysis with percentages. Results: The results of the analysis show that the average score of the four aspects of student interest in learning is 2.7. The percentage of students' interest in learning based on certain aspects is as follows: interest aspect of 65.20% (24%), pleasure aspect of 69.17% (26%), attention aspect of 69.58% (26%), and involvement aspect of 65.30% (24%). Conclusion: Based on these data, students' interest in learning volleyball in class VII is in the medium category.